Education Reconstruction: A Collaboration of Quiz Team and Kahoot Methods in Learning Arabic - Nana Meily Nurdiansyah; Armai Arief; Fentin Ria Agustin; Hudriyah Hudriyah; Muassomah Muassomah; Syaiful Mustofa (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2021)
The purpose of this paper is to start from an educational reconstruction paradigm to support teachers to always innovate in creating innovative teaching methods, especially in learning Arabic, especially in learning that uses technology, given that education is already in the era of the industrial revolution 4.0, where every Human are required to be technology literate. This study uses experimental research Borg & Gall, the focus is to determine the level of influence of treatment on behavior that arises as a result of the treatment and or as a systematic method to build relationships that contain causal-effect relationships. Based on the results of this study it was found that; First, the combination of the Quiz Team-type Active Learning method with Kahoot is the right ingredient to make it easier for students to learn Arabic by training the four maharah or language skills, namely: listening (istima'), reading (qirā'ah), speaking (kalām). , and write (kitābah) at the same time; Second, the results of this study are in the form of design designs, and the role of educators in implementing the collaboration of the quiz team and Kahoot methods in learning Arabic.